A new strategy to construct a FRET platform for ratiometric sensing of hydrogen sulfide. Issue 8 (11th December 2014) - He, Longwei; Lin, Weiying; Xu, Qiuyan; Wei, Haipeng
Abstract : We introduce a new FRET strategy working in coordination with the ICT process to construct a ratiometric fluorescent H2 S sensor. Abstract : We introduce a new FRET strategy to construct a ratiometric fluorescent H2 S sensor. The ratio emission signal of the coumarin–naphthalimide dyad is modulated by the FRET process, which works in coordination with the ICT mechanism. The FRET process on/off is controlled through tuning the overlap level of the donor emission spectrum with the acceptor absorption via modulation of the acceptor fluorophore absorption wavelength.CN-N3 was applied to visualize both the intracellular exogenous and endogenous H2 S through blue and green emission channels.